Structure Based Virtual Docking and Molecular Dynamics Guided Identification of Potential Phytoconstituents from Traditionally Used Female Antifertility Plant - Keerthi Priya; Suman Manandhar; Runali Sankhe; M Manjunath Setty; UV Babu; Sreedhara Ranganath Pai (Tabriz University of Medical Sciences, 2022)
Background: Oral contraceptives are very widely used agents to check unwanted pregnancies.They contain synthetic analogues of estrogen and progesterone hormones. Estrogen is an important hormone that plays a significant role in menstrual cycle, ovulation, fertilization and implantation. Estrogen receptor α (ERα) can modulate the ovulation, fertilization or receptivity of the uterus. Oral contraceptives pose mild to severe adverse effects such as menstrual cycle disorders, metabolic alterations and increased risk of cancers. It is essential to identify and screen alternative contraceptives that are safer to use. The present study was aimed at identifying the compounds from Cissampelos pareira that is traditionally used for antifertility activity. Methods: The compounds reported from the plant were collected and prepared using the LigPrep wizard. The protein, ERα was selected from protein data bank (1G5O) and prepared. The ligands were docked with the protein and the hits were selected for further screening of free energy calculation, induced fit docking and molecular dynamics simulations based on the respective scores and various interactions. Results: Among various compounds, Coclaurine and Norruffscine have been identified to interact with ERα and possess similar interactions as that of the endogenous ligand, estradiol. The compounds also showed drug-like properties in Qikprop analysis and promising result in the molecular dynamics simulation studies. Conclusion: Considering the dock scores, molecular interactions with the ERα receptor and energy calculations, the compounds Coclaurine and Norruffscine were found to have good binding properties. Further in vitro and in vivo evaluations are warranted for confirmation.